Comparison of compressive strength between Trioxide Mineral Aggregate and BiodentineTM in permanent lower molar furcation perforations - Jheymy Gerardo Huatuco-Granda; John Paul Torres-Navarro; Rosa Josefina Roncal-Espinoza (Universidad de Antioquia, 2024)
Introduction: one of the most frequent accidents during root canal access in endodontic treatment is perforation at the level of the pulp floor and bioceramics are currently suggested to repair perforations. The aim of this study was to compare the compressive strength of Mineral Trioxide Aggregate (MTA) and BiodentineTM in furcation perforations of lower permanent molars. Methods: 30 human lower molars were selected, and an endodontic cavity access, were decoronated, and were duly stopped, and then randomly divided into 3 groups (n=10). Group 1: specimens in which a furcation perforation was created and sealed with MTA. Group 2: specimens in which a furcation perforation was created, sealed with BiodentineTM. Group 3: specimens without perforation. After 30 days, they were subjected to compressive forces using a universal testing machine recording the force required to produce the fracture. The data were processed with ANOVA and Tukey statistical tests, with a significance level of p<0.05. Results: the compressive strength of BiodentineTM (190.84 MPa) did not show statistically significant differences with respect to MTA (165.29 MPa) at 30 days of evaluation. However, MTA did show a difference when compared to the control group (213.46 MPa). Conclusion: when evaluating the compressive strength in MPa, BiodentineTM presented similar values in the sealing of lower molar furcation perforations when compared to the control group and MTA; whereas, MTA presented significantly lower results than the control; likewise, the relative difference of the latter group was greater with respect to the others.